Peran Public Relations dalam Meningkatkan Brand Image The Great Asia Africa Lembang - Tevi Tevani; Dadan Mulyana (Bandung Conference Series: Public Relations, 2022)
Abstract. This research is entitled "The Role of Public Relations in Improving the Brand Image of The Great Asia Africa Lembang". This study aims to determine how the role of Public Relations in improving the brand image of The Great Asia Africa Lembang. This study describes two parts, namely the role of public relations and efforts in improving the brand image of The Great Asia Africa Lembang. This study uses qualitative research methods through a case study approach. Data collection techniques used are in-depth interviews, observation, literature study, and documentation related to research. The subject of this research is Intania who represents as Public Relations of The Great Asia Africa Lembang and the supporting informant is Novi as staff of Public Relations Officer of The Great Asia Africa Lembang. The theory used in this research is Public Relations Theory and Brand Image Theory. The results showed that the role of public relations in improving brand image was carried out according to the four categories of the role of public relations, namely expert adviser (expert prescriber), communication facilitator (communication facilitator), problem solving process facilitator, and communication technician. ). Efforts made by public relations in improving the brand image of The Great Asia Africa Lembang are doing promotions through print, electronic and online media. Also making efforts with PR Digital Marketing, establishing relationships with press relations, and forming public opinion by holding social events. Abstrak. Penelitian ini berjudul “Peran Public Relations Dalam Meningkatkan Brand Image The Great Asia Africa Lembang”. Penelitian ini bertujuan untuk mengetahui bagaimana peran Public Relations dalam meningkatkan brand image The Great Asia Africa Lembang. Penelitian ini menjelaskan dua bagian, yaitu peran public relations dan upaya dalam meningkatkan brand image The Great Asia Africa Lembang. Penelitian ini menggunakan metode penelitian kualitatif melalui pendekatan studi kasus. Teknik pengumpulan data yang digunakan adalah wawancara mendalam, observasi, studi kepustakaan, dan dokumentasi yang berhubungan dengan penelitian. Subjek penelitian ini ialah Anugerah yang mewakili sebagai Public Relations dari The Great Asia Africa Lembang dan informan pendukung nya yaitu Novi sebagai staff dari Divisi Public Relations dan Marketing dari The Great Asia Africa Lembang. Teori yang digunakan dalam penelitian ini ialah Teori Public Relations dan Teori Brand Image. Hasil penelitian menunjukkan bahwa peran public relations dalam meningkatkan brand image dilakukan sesuai keempat kategori peran public relations yaitu penasehat ahli (expert prescriber), fasilitator komunikasi (communication facilitator), fasilitator proses pemecahan masalah (problem solving process facilitator), dan teknisi komunikasi (communication technician). Upaya yang dilakukan public relations dalam meningkatkan brand image The Great Asia Africa Lembang yaitu melakukan promosi melalui media cetak, elektonik dan online. Juga melakukan upaya dengan PR Digital Marketing, menjalin hubungan dengan press relations, dan pembentukan opini publik dengan melaksanakan event social.